Construction of Pencil Graphite Electrode Modified with Nafion, MWCNT, and Bismuth for Simultaneous Lead and Cadmium Detection - Ustabasi, Gul Sirin; Yilmaz, Ismail; Ozcan, Mustafa; Cetinkaya, Ebru (ELECTROCHEMICAL SOC INC, 2021)
Carbon based electrodes (CBE) demonstrate outstanding performance in electroanalytical procedures. Having a large surface area, high conductivity, and low cost, disposable pencil graphite electrodes (PGE) are an exceptional type of CBE. In this study, PGE were modified with Nafion and multiwall carbon nanotube via dip-coating (MWCNT/N/PGE) and with bismuth via in situ plating (MWCNT/N/Bi/PGE). Furthermore, electrochemical and surface characteristics of the MWCNT/N/PGE were investigated by scanning electron microscopy, cyclic voltammetry, and electrochemical impedance spectroscopy measurements. The MWCNT/N/Bi/PGE was employed in the simultaneous voltammetric detection of Pb2+ and Cd2+ in environmental samples via Square Wave Anodic Stripping Voltammetry (SWASV) and generated compatible results with Graphite Furnace Atomic Absorption Spectrometry (GFAAS) technique. Detection limits for lead and cadmium ions were obtained as 0.37 and 0.32 mu g l(-1), respectively. This sensitive method coupled with a highly selective electrode also provided wide linear ranges for Pb2+ and Cd2+ between 1-100 mu g l(-1) and 1-90 mu g l(-1), respectively. Main advantage of this method lies in the simplicity and the efficiency of the modification process. The modification method described in this study conserves the valuable time of the analyst and produces electrodes that present excellent analytical performance. (c) 2021 The Electrochemical Society (ECS). Published on behalf of ECS by IOP Publishing Limited.
Keywords: VOLTAMMETRIC DETERMINATION; GLASSY-CARBON; METAL-IONS; STRIPPING VOLTAMMETRY; COMPOSITE; NANOCOMPOSITE; CD(II); PB(II); SENSOR; CD; Electrochemistry; Materials Science